Improving Long-Term Care Facilities’ Crisis Response: Lessons from the Covid-19 in Chile - Villalobos-Dintrans, P (LSE Press, 2021)
Context: The COVID-19 pandemic hit Chile hard and affected older people the most. Through its National Service for Older Adults, the country implemented a strategy to prevent and mitigate infection and spread in long-term care facilities (LTCF), reaching regulated and registered residences and, for the first time, informal and unregistered residences. Objective: Identify the challenges and lessons from the COVID-19 response in LTCF with respect to the support received, the implementation of infection control measures, workforce challenges experienced and the measures adopted to promote residents’ wellbeing. Methods: An online questionnaire was sent to all LTCF managers (N = 385, Response Rate = 32.4%). Statistical tests compare results to identify differences across LTCF characteristics: residence size, location and management type (private, public or subsidized, or informal). Findings: Irrespective of their location, size or management, managers highlight common challenges during the crisis. They include limited personal protective equipment (PPE) availability, staff shortages, low quality of replacement staff, reduced staff mental health, and the difficulty to understand and implement protocols. Managers acknowledge receiving institutional support in the form of PPE provision and opportunities for staff training, but managers noted the need to expand this support to cover staffing surge needs, staff psychological needs, and ensure the continuity of clinical support for residents as well. Managers share a common demand for a more coordinated response from public institutions. Managers recognize that the pandemic and the measures implemented to mitigate it negatively affected staff morale and residents’ wellbeing. Many noted that peer-to-peer support was a mechanism to support staff. Limitations: Results might be subject to selection bias. Data collection covered a limited period of time at the early stage of the pandemic. Implications: Findings are relevant to assess the COVID-19 response and to better prepare for another COVID-19 wave or similar health or environmental threats in the future. © 2021 The Author(s).